Incidence of Gum Bleeding in Patients Taking Antiplatelet Therapy - Muhammad Ahmad, Shafaq Mannan, Sibgha Aziz, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Medical practitioners often advise patients on antiplatelet therapy to either stop or alter their medications prior to invasive surgical procedure because of fear of excessive and uncontrolled bleeding. Objectives: The main objective of the study is to analyse the incidence of gum bleeding in patients taking antiplatelet therapy among local population of Pakistan Material and methods: This descriptive study was conducted in Saddique Family Hospital Gujranwala during June 2020 to December 2020. After permission from hospital ethical committee, total 120 patients meeting the inclusion and exclusion criteria will be enrolled in the study from Saddique Family Hospital Gujranwala. Detailed history and physical examination will be done to meet the inclusion and exclusion criteria. Informed consent will be obtained. Internal bleeding included hematoma, epistaxis, vaginal bleeding, melena, hematemesis, eye bleeding, and haematuria. Results: The data was collected from 120 patients. The mean age was 35.67±2.56 years. The mean BT was 19.5 ± 5.2 min, ranging from 5 min to more than 20 min. The incidence of bleeding was 32%. Seventeen patients had a BT longer than 20.5 min and less than 26 min: 5 nuisance bleeding and 1 internal bleeding (mild hematuria) which stopped after discontinuation of platelet inhibitory agents. Conclusion: It is concluded that available evidence suggests that most dental interventions can be safely performed without the interruption of antithrombotic therapy.